POTENSI DAYA DUKUNG LIMBAH TANAMAN PALAWIJA SEBAGAI PAKAN TERNAK RUMINANSIA DI KABUPATEN PRINGSEWU - Sari, Anita; ,, Liman; ., Muhtarudin (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2016)
The aims of the research to determine the carrying capacity of waste by product and livestock based agriculture waste as feed for ruminants in District Pringsewu . This study used a survey method. The survey method used in this research is purposive sampling. Potential feed material is calculated based on the production of feed material multiplied by the area harvested and expressed in dry matter (DM ) , crude protein (CP ) and total digestible nutrients ( TDN ) . Forage samples obtained from taking snippets / tiling agricultural waste. The results showed that the production of waste in dry matter by BK , PK , and TDN respectively is 170 420 tonnes , 13 296 tonnes and 86 600 tonnes . Then the carrying capacity (DDLP ) based BK , PK , and TDN Â is 74 672 UT , UT 5519 and UT 55 195 . Total population of ruminants in District Pringsewu ( 20 804 UT ) can be met the needs of feed based on availability BK , and TDN . Keywords : District Pringsewu , Waste Production , Livestock Ruminant , Carrying Food Waste